(untitled) (International Journal of Engineering and Computer Science, 2018)
As a result of the tremendous growth of the World Wide Web, the raw web data has become a vast source of information. Nowadays, the usages of search engines are considerably high by all types of users. The information required by different group of users are collected and represented by different types of search engines from many other sources. Web robot is one of the strategies which is used by many search engines as well as many other websites for collecting their data from the respective websites. These web robots are useful for many application, these are also dangerous for websites due to extracting the information of a particular site in an unauthorized way. In this paper, We are suggesting the association rule mining algorithm named as "Optimized Distributed Association Mining" Algorithm for identifying the web robots which trying to traverse through website’s confidential page or content and want to extract that content and after identifying ODAM will remove that web robot program. In such a way ODAM will help to prevent the websites from unauthorized access and other malicious programs.